The Chicken Slaughterhouse in Jember City, Mapping the flesh Total Plate Count, pH, Lactic Acid, and Tetracycline Antibiotics of The Chicken - Margayu, Galuh Risxi; Kalsum, Umi; Ali, Usman (MultiTech Publisher, 2024)
TThe study's objective was to map the total plate count (TPC), pH, lactic acid, and antibiotic residues, including tetracycline, in broiler meat from the Patrang sub-district in the Jember district. The study employed a descriptive case study methodology and employed ANOVA and the BNT test for data analysis. Significant effects on lactic acid, pH, and microbiological parameters were discovered by the research. Three conventional RPAs did not contain any traces of the antibiotic tetracycline. The investigation came to the conclusion that SNI guidelines and Standard Operating Procedures (SOP) for chicken slaughter were met by the level of antibiotics, lactic acid, pH, TPC, and tetracycline in RPA in Jember City's Patrang environment.